2017
DOI: 10.1109/tps.2017.2715558
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Simulation Study of Electron Holes Dynamics During Collisions of Ion-Acoustic Solitons

Abstract: Abstract-Ion acoustic (IA) solitons are accompanied by vortex-shaped nonlinear structures (e.g. hollows, plateaus or humps) in the electron distribution function, called electron holes, portraying trapped electrons. These structures appear as charged flexible clouds (shielded by the background plasma) in the phase space with their own inertia, depending on the number of trapped electrons. According to simulation studies, electron holes tend to merge in pairs until one accumulative hole remains in the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…The one-dimensional PIC simulation in Ref. [12] showed that for plasma conditions similar to the ones we use here electron phase space holes form, which are connected to ion solitary waves [17]. Here we have shown that such solitary waves grow to a large amplitude also in a 2D simulation.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The one-dimensional PIC simulation in Ref. [12] showed that for plasma conditions similar to the ones we use here electron phase space holes form, which are connected to ion solitary waves [17]. Here we have shown that such solitary waves grow to a large amplitude also in a 2D simulation.…”
Section: Discussionsupporting
confidence: 58%
“…6(a) and also for an electron phase space hole, which corresponds to a localized positive excess charge around which the electrons oscillate. Both non-linear plasma structures often coexist and the ion acoustic wave lends the electron phase space hole additional stability [17]. Protons at the wave crest at y ≈ 1.98 in Fig.…”
Section: Figure 1 Provides An Overview Of Plasma Evolution Bymentioning
confidence: 97%
See 2 more Smart Citations
“…Ion acoustic waves are linearly undamped if the ratio between the electron temperature and ion temperature is large [4], which is the case in our simulation after the Buneman instability has saturated. We note, however, that the presence of the electron phase space holes means that the ion velocity oscillations may not be linear since electron phase space holes and large ion acoustic waves can couple [31].…”
Section: Phase Space Density Distributionsmentioning
confidence: 87%